2020
DOI: 10.1002/adfm.202004037
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion Lattice Phases in Thin Film Multilayer

Abstract: Phases of matter are ubiquitous with everyday examples including solids and liquids. In reduced dimensions, particular phases, such as the 2D hexatic phase and corresponding phase transitions occur. A particularly exciting example of 2D ordered systems are skyrmion lattices, where in contrast to previously studied 2D colloid systems, the skyrmion size and density can be tuned by temperature and magnetic fields. This allows for the system to be driven from a liquid phase to the onset of a hexatic phase as deduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 34 publications
(69 reference statements)
4
40
2
Order By: Relevance
“…[ 34,35 ] and [ 37 ] and were also used in our previous work. [ 14,25 ] We neglect any effects of a nonflat energy landscape, which can be observed in some of the experiments, in our idealized simulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 34,35 ] and [ 37 ] and were also used in our previous work. [ 14,25 ] We neglect any effects of a nonflat energy landscape, which can be observed in some of the experiments, in our idealized simulations.…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] and [37] and were also used in our previous work. [14,25] We neglect any effects of a nonflat energy landscape, which can be observed in some of the experiments, in our idealized simulations. As shown in Figure 2b, arrangements with triangular symmetry arise for all investigated numbers of skyrmions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[88] In the absence of any (effective) attractive interactions between such passive colloidal particles, no phase transitions whatsoever are expected in such a colloidal suspension in equilibrium, apart from entropy-driven crystallization [87] at high densities of the colloids (when the typical distance between the particles is of the order of the colloid diameter) and potentially an intermediate hexatic phase in two-dimensional systems. [89][90][91] However, the situation changes fundamentally when we give the Brownian particles a velocity ṽ i of fixed absolute value v 0 , like in the Vicsek model. The direction [4] © IOP publishing.…”
Section: Selected Models For Active Matter Systemsmentioning
confidence: 99%
“…This turns them into attractive candidates for applications in novel devices relying on skyrmion-based logic [15,16], Brownian computing [17,18] and racetrack memory [3,[19][20][21][22]. High density lattice states, in which skyrmions strongly interact with each other, have recently moved into the focus of attention [8,[23][24][25][26]. In contrast to colloids [27][28][29], sizes and density of skyrmions can be adjusted on the fly which makes them ideal model systems to study phase behaviour in two dimensions [30] as demonstrated by the demonstration of hexatic and solid phases in Refs.…”
mentioning
confidence: 99%